INTEGRATED QUALITY MANAGEMENT TO CREATE A SCHOOL AS A CENTER OF EXCELLENCE AT JUNIOR HIGH SCHOOL IN BANDUNG CITY (Description Study at SMP Negeri 5 and SMP Negeri 3 Bandung) - Ridwan Nurpalah; Sutaryat Trisnamansyah; Hanafiah; Ida Tejawiani (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2022)
Schools are providers of formal education and centers of excellence for human empowerment. Salis stated that Integrated Quality Management (MMT) is “a philosophy of continuous improvement methodology, which provides a set of practical tools for every educational institution in meeting the needs, wants, and expectations of customers, current and future”. In general, the purpose of this study is to describe and analyze the concept of developing quality schools as MMT-based centers of excellence with the development of excellent services. This study uses a qualitative approach and data sources through interviews, observations and documentation through the principal, vice principal, teachers, and students. The results of data analysis showed that the principal's leadership in implementing MMT in SMP Negeri 5 and SMP Negeri 3 Bandung was quite effective in accordance with school planning. This is marked by the principal's continuous efforts to make improvements and changes as a whole in achieving quality, so that schools are realized as a source of excellence. The general conclusion is that the principal has management capabilities that are implemented in schools as a place for comfortable, harmonious, fun and quality education, as well as being highly competitive and having effective management supported by superior human resources to produce superior human resources with target achievement. set.